Steadfast Ayurvedic Management in Hypothyroidism (AYUSHDHARA, 2024)
Hypothyroidism is an endocrine disorder that mainly occurs due to insufficient thyroid gland stimulation or primary gland failure by pituitary or hypothalamus gland. It is estimated to have affected 2-5% of world population. It is quite challenging to decipher the symptoms of hypothyroidism from other systemic disorders as they have quite similar presentation. The chaotic lifestyle, faulty food habits, reduced physical activity, over exertion at work, subjection to various environmental changes have created a vicious cycle disrupting the endocrine functioning of body. With rapid rise in incidence, dependency on lifelong thyroid hormone replacement therapy is preferred. Ayurveda being ancient system of medicine is highly efficient in healing the endocrine dysfunction. In context of Ayurvedic review the symptoms of hypothyroidism clearly depicts the involvement of Mandha agni. This particular case can be correlated with Galaganda. Case intervention: A 50-year-old- female patient visited the ENT OPD of Patanjali Ayurveda Hospital, Haridwar, with diffuse thyroid swelling and the thyroid profile test revealing increased TSH level of 8.12 uIU/ml for 12 years. The patient presented with USG neck suggestive of diffuse thyroid nodule. She earlier visited various allopathic clinics and was diagnosed with hypothyroidism and was currently taking Thyroxine sodium tablet 75 mcg. Conclusion: Ayurvedic protocol aimed at holistic approach by pacifying the vitiated doshas and showing significant reduction in level of TSH and providing symptomatic relief. It helped the patient in withdrawing from dependency on thyroid hormone replacement medicines.